STRATEGIC MANAGEMENT IN CAR OWNERSHIP AND PURCHASE DECISION IN JAKARTA - Mawardi, Izhari (Academic Research Centre Services, 2017)
The automotive industry is one of the most lucrative market in Jakarta, Indonesia. There are opportunities coming from the low car density, a growing number of middle class and the first-time buyers in Jakarta. On the other hand, there are also challenges car manufactures face that could curtail car sales such as, the presence new public transport, the increase on vehicle tax, and the existence of online taxis. Currently, studies related to car ownership motivation according to the future generation of buyer are still limited. Therefore, this study examined the significance between car ownership deterrents, car ownership motivation, and car purchase decision. This study also analysed the preference of cars according to young people, being the future generation in Jakarta. The final objective was to provide PT XYZ a selection of strategies to anticipate such phenomena. The methodology used was Structural Equation Modelling. The result revealed that car ownership motivation and car purchase decision were significantly correlated, while car ownership motivation and car ownership deterrents showed otherwise. Car attributes such as safety, performance, and convenience were considered as the most important criteria according to young people. The managerial implication for PT XYZ is to consider market penetration, market development, and product development. Keywords? Car ownership motivation, Car ownership deterrents, Car purchase decision, Structural Equation Modelling, Strategic Management